Human macrophages and monocyte-derived dendritic cells stimulate the proliferation of endothelial cells through midkine production. - Elias A Said; Sumaya Al-Dughaishi; Wadha Al-Hatmi; Iman Al-Reesi; Marwa Al-Riyami; Mohammed S Al-Balushi; Atika Al-Bimani; Juma Z Al-Busaidi; Murtadha Al-Khabori; Salam Al-Kindi; Francesco A Procopio; Afrah Al-Rashdi; et al. (PLoS ONE, 2022)
The cytokine midkine (MK) is a growth factor that is involved in different physiological processes including tissue repair, inflammation, the development of different types of cancer and the proliferation of endothelial cells. The production of MK by primary human macrophages and monocyte-derived dendritic cells (MDDCs) was never described. We investigated whether MK is produced by primary human monocytes, macrophages and MDDCs and the capacity of macrophages and MDDCs to modulate the proliferation of endothelial cells through MK production. The TLR stimulation of human monocytes, macrophages and MDDCs induced an average of ≈200-fold increase in MK mRNA and the production of an average of 78.2, 62, 179 pg/ml MK by monocytes, macrophages and MDDCs respectively (p < 0.05). MK production was supported by its detection in CD11c+ cells, CLEC4C+ cells and CD68+ cells in biopsies of human tonsils showing reactive lymphoid follicular hyperplasia. JSH-23, which selectively inhibits NF-κB activity, decreased the TLR-induced production of MK in PMBCs, macrophages and MDDCs compared to the control (p < 0.05). The inhibition of MK production by macrophages and MDDCs using anti-MK siRNA decreased the capacity of their supernatants to stimulate the proliferation of endothelial cells (p = 0.01 and 0.04 respectively). This is the first study demonstrating that the cytokine MK is produced by primary human macrophages and MDDCs upon TLR triggering, and that these cells can stimulate endothelial cell proliferation through MK production. Our results also suggest that NF-κB plays a potential role in the production of MK in macrophages and MDDCs upon TLR stimulation. The production of MK by macrophages and MDDCs and the fact that these cells can enhance the proliferation of endothelial cells by producing MK are novel immunological phenomena that have potentially important therapeutic implications.